An international study of the pension system for the Mexican pension regime - Español, Español (2023)
The governments of the countries of the world seek to support the beneficiaries of pension system that are applicable in the unproductive stage of retirement; sometimes this purpose is not achieved, bringing with it reflections on whether a pension system is appropriate. Thus, the objective of this study was to analyze the pension system of countries of the European Union, the United States and Canada, Brazil and Chile, to compare with the pension scheme of Mexico, the AFORES, and quantify the value of the pension, to make a proposal to improve the individual account system pension.  The time series quantitative model was applied for the prediction of an individual account of a generation 70-74 worker, that contributes on the defined benefit system. The result of the study shows that the pension system does not favour a beneficiary with a pension that guarantees his or her quality of life. The contribution of this work lies on making a proposal with recommendations, consistent with the policies of the pension system of the researched countries, and that can be established in the current system.